Turmeric rhizomes reduced in vitro methane production and improved gas production and nutrient degradability - Ahmed E. Kholif; Olurotimi A. Olafadehan; Gouda A. Gouda; Mahmoud Fahmy; Tarek A. Morsy; Hajer Ammar; Hatem A. Hamdon; Mireille Chahine (Animal Biotechnology, 2024)
The present study aimed to evaluate the effect of dry turmeric rhizomes on in vitro biogas production and diet fermentability. Turmeric rhizomes were included at gradually increased levels: 0, 0.5, 1, 1.5 and 2% of a diet containing per kg dr matter (DM): 500 g concentrate feed mixture, 400 g berseem hay and 100 g rice straw, and incubated for 48 h. Gas chromatography-mass spectrometry analysis showed that ar-turmerone, α-turmerone and β-turmerone were the major bioactive compounds in the rhizomes. Turmeric rhizomes increased (p < 0.01) asymptotic gas production (GP) and rate and lag of CH4 production and decreased (p < 0.01) rate of GP, lag of GP, asymptotic CH4 production and proportion of CH4 production. Turmeric rhizome administration linearly increased (p < 0.01) DM and fiber degradability and concentrations of total short-chain fatty acids, acetic and propionic acids and ammonia-N and quadratically (p < 0.05) decreased fermentation pH. It is concluded that including up to 2% turmeric rhizomes improved in vitro ruminal fermentation and decreased CH4 production.